The role of informal capital on new venture formation and growth in China - Elston,Julie; Chen,Sandy; Weidinger,Alois (Small Business Economics, 2016)
This study examines the nature and role of informal capital used by micro-firms in the dynamic emerging market of China. Using a unique source of data for 260 urban entrepreneurs, this study provides empirical evidence that entrepreneurs’ personal savings and family funding are important sources of start-up capital. However, household income is the most important funding source in driving firm growth over time. This research directly addresses the lacuna of studies on entrepreneurship in emerging economies and contributes to our understanding of the critical role informal capital plays in the Chinese entrepreneurial process. Overall findings suggest that informal capital is still predominantly used over formal capital sources for financing firm start-up, underscoring the slow transition in China from an emerging to a modern economy.
Keywords: Accounting; Finance; OSU-Cascades; OSU-Cascades Hospitality Mgt

The Role of Internationalization and Geographic Location - Weidinger,Alois (34th International Business Research Conference, 2016)
Keywords: Accounting; OSU-Cascades

The Role of Internationalization and Geographic Location - Weidinger,Alois (33rd Annual International Business Research Conference, 2016)
Keywords: Accounting; OSU-Cascades

The Role of Informal Capital in Growth in China - Weidinger,Alois (World Conference on “Entrepreneurship at a Global Crossroads”, 2015)
Keywords: Accounting; OSU-Cascades

The role of internationalization and geographic location on entrepreneurial intention: empirical evidence from China - Weidinger,Alois (World Conference on “Entrepreneurship at a Global Crossroads”, 2015)
Keywords: Accounting; OSU-Cascades